Comparison of different molds (epoxy, polymer and silicon) for microfabrication by hot embossing technique - Gupta, A. (2013)
In the fabrication of microfluidic devices by hot embossing, secondary molds made from epoxy and other polymeric materials with high Tg are commonly used in lab-scale research and for short production runs of several hundred products. However, few studies have been conducted to compare the performance and efficacy of such molds compared to the master silicon mold. To allow such molds to be exploited fully, this study investigates the performance of silicon, epoxy and COC (TOPAS-6017 grade) molds to fabricate microchannels on COC (TOPAS-8007 grade) substrate using hot embossing. The degree of filling of the mold cavity during microfabrication was assessed. At the optimum embossing conditions (i.e. 100 °C, 2.94 kN load and 5 min loading time), all three molds had similar performance in terms of replication fidelity. However, at sub-optimum conditions (e.g. 80 °C), the silicon mold was the best in terms of mold cavity filling followed by COC and epoxy. For surface roughness and friction coefficient which are important factors affecting tool life, it was found that epoxy mold gives the lowest values followed by COC and silicon. The surface energy determined using contact angle measurements gave a similar trend with epoxy having the lowest surface energy (28 dyne/cm), followed by COC (33.52 dyne/cm) and silicon (71.63 dynedyne/cm). A lower surface energy will result in lower adhesion and friction coefficient between the polymer and mold, resulting in easier demolding.